An artificial magnetic ground-plane for a log-periodic antenna - Visser, Hugo Hendrik (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.